2009
DOI: 10.1007/s00425-009-0970-y
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium decreases crown root number by decreasing endogenous nitric oxide, which is indispensable for crown root primordia initiation in rice seedlings

Abstract: Cadmium (Cd) is toxic to crown roots (CR), which are essential for maintaining normal growth and development in rice seedlings. Nitric oxide (NO) is an important signaling molecule that plays a pivotal role in plant root organogenesis. Here, the effects of Cd on endogenous NO content and root growth conditions were studied in rice seedlings. Results showed that similar to the NO scavenger, cPTIO, Cd significantly decreased endogenous NO content and CR number in rice seedlings, and these decreases were recovera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…The activities of NOS and NR were determined with the NOS Assay Kit and the Nitrate/Nitrite Assay Kit (Beyotime) with some modifications (Xiong et al, 2009). Total protein was extracted using buffer containing 100 mM HEPES-KOH (pH 7.5), 1 mM EDTA, 10% glycerol, 5 mM dithiothreitol, 0.1% Triton X-100, 0.5 mM PMSF, 20 mM FAD, 25 mM leupeptin, 5 mM Na 2 MoO 4 , and 1% polyvinylpyrrolidone.…”
Section: Determination Of Nos and Nr Activities And Nitrate Contentmentioning
confidence: 99%
“…The activities of NOS and NR were determined with the NOS Assay Kit and the Nitrate/Nitrite Assay Kit (Beyotime) with some modifications (Xiong et al, 2009). Total protein was extracted using buffer containing 100 mM HEPES-KOH (pH 7.5), 1 mM EDTA, 10% glycerol, 5 mM dithiothreitol, 0.1% Triton X-100, 0.5 mM PMSF, 20 mM FAD, 25 mM leupeptin, 5 mM Na 2 MoO 4 , and 1% polyvinylpyrrolidone.…”
Section: Determination Of Nos and Nr Activities And Nitrate Contentmentioning
confidence: 99%
“…It was demonstrated that about 70-90% of the heavy metal in cells was located in the cell walls and was prevented from entering the cytoplasm in Athyrium yokoscense (Nishizona et al 1987). Although a few authors have reported the eVect of exogenous NO on alleviating Cd toxicity by decreasing oxidative stress or recovering decrease of crown root number in rice seedlings (Hsu and Kao 2004;Xiong et al 2009), many other mechanisms of exogenous NO in alleviating Cd toxicity are still far from clear.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, it has been shown that treatment with 50 μM Cd 2+ for 48 h significantly decreases NO in Medicago truncatula roots and treatment with 50 μM Cd 2+ for 14 days also produces a significant reduction of NO content in the roots and leaves of P. sativum (Rodríguez-Serrano et al 2009;Xu et al 2010a). In addition, a 24-h treatment with 100 μM Cd 2+ significantly decreases the NO content in the crown roots of 7-day-old rice seedlings, and in crown roots of 4-week-old plantlets a 0.2 mM Cd 2+ stress induces, after a rapid increase in the first half-hour, a strong and progressive decrease in the NO level (Xiong et al 2009b). …”
Section: No Generation Under Hms Stressmentioning
confidence: 95%
“…For example, it was attributed to differences in the cell responses to short and long periods of metal treatment, a short-time HM treatment leading to a NO burst, and a long-time treatment directly or indirectly decreasing NO generation (Rodríguez-Serrano et al 2009). Another explanation could be the use of different HM concentrations, the age of the plants, and the variety of plant tissues used (Groppa et al 2008;Xiong et al 2009b). In addition, it should also be noted that NO can rapidly react with oxygen to produce a variety of nitrogen oxides, so the local concentration of NO depends on a complex balance among its concentration, system redox state of the cells, and the utilization of NO by its target molecules and metals (Lamattina et al 2003).…”
Section: No Generation Under Hms Stressmentioning
confidence: 98%